EFFECT OF STRAIN AND BEE POPULATION AND METHOD OF PROPOLIS COLLECTING IN SOME BIOLOGICAL CHARACTERS OF HONEY BEE COLONIES APIS MELLIFERA L. DURING THE AUTUMN SEASON UNDER MOSUL PROVINCE / IRAQ - Muzahim A. Elsaiegh; Mohammed K. Ibrahim (Mesopotamia Journal of Agriculture)
All studies were conducted during the period from 31/8/2012 - 17/11/2012 in the bee apiary and bees lab of Plant Protection Department / college of Agriculture and Forestry - University of Mosul on the hybrid local bee colonies and Iranian Caucasian bee colonies. The results showed that the highest mean of bee population reached 8.708 bee frame in the treatment of alocal hybrid strain 10 frame population ( S L H P - 10 ) compared with the Caucasian strain (S C I P 10) but in the population of Five bee Frames the highest mean was 4.291 frame in S L H P 5 treatment compared to S C I P 5 treatment which recorded the lowest mean.The S L H P 10 recorded the highest mean of worker brood which was 75.78 sq. inches compared with the lowest mean recorded in S C I P 10 treatment , but in the treatment of S C I P 10the highest mean was 61.22 sq. inches in the S L H P 5 treatment compared with 48.11 sq. inches in the S C I P 5 treatment, about of the pollen area, The S L H P 5 gave the higest mean 25.44sq. inches in compared to the S C I P 5 treatment which recorded the lowest mean 12.442sq. inches but for the treatment of 10 frame population, S L H P 10 treatment gave the highest mean of 27.995sq. inches which did not differ significantly from S C I P 10 and S L H P 5 treatments. About unsealed honey area there were no differences between treatments, but S L H P 5 gave the highest mean 184.665 sq. inches, also S L H P 10 treatment gave the highest mean 367.83sq. inches compared with S C I P 5 and S C I P 10, which they recorded the lowest mean, also the above treatment gave the highest mean of sealed honey area 349.882 and 643.497 sq. inches respectively compared with S C I P 5 and S C I P 10. Highest mean of propolis recorded in S C I P 5 and S C I P 10 3.661 and 9.388 gm. respectively compared, With the lowest mean which recorded in S L H P 5 and S L H P 10 . All the above means were recorded under ambient temperature and relative humidity of 25.69ºC and 43.25%, respectively.